Preliminary Analysis of The Determinants of SMEs Performance (Global Business Management Review (GBMR), 2022)
Preliminary analysis is the inspection, scrutiny and analysis conducted on data before main analysis, to detect, manage and correct/treat errors. Preliminary analysis helps in data screening, cleaning, initial examination and correcting/treating incorrect entries, identify outliers, missing values and to identify other unusual entries in dataset. Although, preliminary analysis is vital in academic research, majority of researchers partially report, or entirely do not perform and report this stage in their studies. Evading this critical stage of research could lead to poor quality and incorrectness of the research results and misinterpretation due to under or over inflation of statistical results. Unexpectedly, the review of the extant literature discovered that there is scarcity of studies that have been conducted and reported on preliminary analysis. This has limited scholars, educators and other stakeholders in understanding the importance of conducting and reporting preliminary analysis in enhancing reliability and accuracy of research results, findings, interpretation and implications. Consequently, this research filled in these gaps by developing a framework and providing empirical evidence on these issues. This would be of great benefits to the academic world. Thus, the results indicated that the data had met all the criteria and assumptions for multivariate analysis after statistical analysis and treatment. Thus, it is recommended that studies in entrepreneurship, social sciences, management and other related disciplines should apply and follow this procedure to help in meeting the criteria for multivariate data analysis.